The Demise of Modernist Buildings in Khor Dubai: A Case Study on the FNCB Building - Rasha Saffarini (ARCHive-SR)
Khor Dubai, or Dubai Creek, is the historic district that went through the first layer of development before the urban expansion to the desert. It witnessed profound architectural transformations in three economic phases:  the pearl trade, oil discovery, and real estate. Today, early modernist buildings have been replaced with high-rise buildings to meet the financial demands of real estate. This replacement has been a rapid process, making it difficult for the Modern Heritage Initiative of Dubai (MHID) to cease it. In the creek, the First National City Bank building (FNCB) is one of the buildings that marked modernity yet failed the test of time. This study aims to illustrate the economy’s impact on Dubai’s modern heritage, focusing on the FNCB. It also identifies the issues that hinder preserving the architectural heritage of smaller buildings. A descriptive research methodology is employed for this study using visual analysis, site visits, and conversations to illustrate the rise and fall of modernist structures. The findings establish that due to Dubai’s fast-paced growth, replacing heritage is more profitable to sustain the ever-growing demands of Dubai as a real estate hub. It also discusses the importance of immaterial and material values historic buildings hold despite how insignificant they seem now.